Homocysteine: cardiovascular risk factor in children and adolescents? - Leal,Adriana Amorim De Farias (2013)
The aim of this study was to identify publications in literature that investigated Homocysteine (He) as a risk factor for CVD among children and adolescents. An active search for information in LILACS, IBECS, Science Direct, Medline and Cochrane Library databases was conducted using the following combination of keywords "homocysteine", "cardiovascular diseases", "child" and "adolescent". Fifteen articles were analyzed showing direct relationship with increasing age (8 studies) and male gender (10 studies), and an inverse relationship with serum vitamins B6, B12 and folate levels. Thus, the results suggest that more research must be carried through in order to determine in a more coherent way the causes of the hiperhomocisteinemia in the pediatric population, guiding for an adequate diet, rich in nutrients necessary to favor the metabolism of the He.